Torn - David Massey (Chicken House, 2012)
Afghanistan. In the heat and dust, young British Army medic Elinor Nielson watches an Afghan girl walk into a hail of bullets. But when she runs for help, Ellie finds her gone. Who is she? And what's happened to her? What Ellie discovers leads her to question everything she believes in - even her feelings for the American Lieutenant who take her side